Anti-static BOPET (Biaxially Oriented Polyethylene Terephthalate) film for enhancing UV printing adhesive force and coating material
By using modified polythiophene antistatic agent and aqueous UV curing resin coating materials on the BOPET film, combined with online coating technology, the problems of low adhesion and electrostatic electricity of UV ink are solved, and high adhesion and antistatic properties are achieved. BOPET membrane.
Patent Information
- Application Number
- CN202411681365.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyester film coating for UV ink printing has low adhesion, easy ink to fall off, and PET has a high static electricity, making it impossible to cooperate with high-speed printing.
The coating material made of a modified polythiophene antistatic agent and an aqueous UV curing resin is formed on the BOPET film through an online coating technology to enhance the adhesion of UV.
It significantly improves the adhesion between UV ink and the coating, ensuring good ink adhesion in high humidity environments, and the coating has good antistatic properties to meet the needs of high-speed production.
Smart Images

Figure BDA0005148421850000021 
Figure BDA0005148421850000031 
Figure BDA0005148421850000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging printing films, and in particular relates to an antistatic BOPET film with enhanced UV printing adhesion, and also relates to a coating material for preparing the antistatic BOPET film with enhanced UV printing adhesion. Background Art
[0002] BOPET film (biaxially oriented polyester film) is a polyester film made from polyethylene terephthalate (PET) through melt extrusion, longitudinal stretching, transverse stretching, traction and winding. Polyester film is a non-polar material with low surface energy and poor wetting properties, making it difficult for ink to adhere.
[0003] In order to make the printing quality meet the use requirements, the polyester film needs to be pre-treated before use to increase its surface free energy. The most commonly used treatment methods are corona treatment and surface coating printing enhancement coating treatment. For example, a method for manufacturing a polyester film is provided in a patent application with publication number CN106891514A, in which the surface adhesion ability of the polyester film can be enhanced by performing double-sided corona treatment on the polyester film after stretching. Although the corona treatment scheme can increase the surface tension of the film, the treatment effect is time-sensitive, especially in high temperature and high humidity environments, the surface tension decays seriously, and it is difficult to meet most printing quality requirements. The use of printing enhancement coating treatment can ensure that the surface tension is maintained for a long time and broaden the adaptability of printing inks. Compared with traditional inks, UV inks have the advantages of not containing volatile organic compounds (VOCs), less environmental pollution, fast curing speed, energy saving, and being suitable for high-speed automated production. However, since the photoinitiator in the UV ink is irradiated by ultraviolet light, free radicals or cations are generated to initiate polymer curing, and the curing time is short, the problem of low adhesion of UV ink on the film surface will be caused. Currently, commonly used printing enhancement coatings are polyacrylate and polyurethane resins. For example, the patent application with publication number CN116285543A discloses an enhanced UV ink printing film to improve the problem of insufficient adhesion of UV ink on the surface of polyolefin film. However, since the film is easily affected by static electricity, it cannot be used with high-speed ink printing (such as ink printing at a speed of 100m / min or above), so its use is greatly limited.
[0004] Aiming at the problems that the existing polyester film coating for UV ink printing has low adhesion, the ink is easy to fall off, and the PET has high static electricity and cannot be used for high-speed printing, the present invention aims to provide an antistatic BOPET film with enhanced UV printing adhesion. Summary of the invention
[0005] The object of the present invention is to provide an antistatic BOPET film for enhancing UV printing adhesion. At the same time, the object of the present invention is also to provide a coating material for preparing an antistatic BOPET film for enhancing UV printing adhesion.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions.
[0007] In a first aspect, the present invention provides a coating material, which is made of the following raw materials in percentage by weight:
[0008]
[0009]
[0010] As an embodiment of the present invention, the preparation method of the modified polythiophene antistatic agent is: adjusting the pH value of the poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion stock solution to 7.3-7.6 with ammonia water, then mixing it with an aqueous polyurethane resin emulsion, a titanate coupling agent and isopropanol, and then diluting it with water to obtain the modified polythiophene antistatic agent.
[0011] As an embodiment of the present invention, the mass ratio of the poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid aqueous dispersion stock solution, the aqueous polyurethane resin emulsion, the titanate coupling agent, and the isopropanol is: (1-5): (10-20): (0.1-1): (10-30).
[0012] As an embodiment of the present invention, the solid content of the modified polythiophene antistatic agent is 10% to 20%.
[0013] As an embodiment of the present invention, the aqueous polyurethane resin emulsion is selected from anionic aqueous polyurethane resin emulsion and nonionic aqueous polyurethane resin emulsion.
[0014] As an embodiment of the present invention, the water-based UV curable resin is a polyurethane anion resin modified by pentaerythritol triacrylate.
[0015] As an embodiment of the present invention, the preparation method of the water-based UV curable resin is as follows: 100 parts by weight of isophorone diisocyanate (IPDI), 90 to 95 parts by weight of polypropylene glycol (PPG-1000), and 0.1 to 0.5 parts by weight of dibutyltin dilaurate catalyst are stirred at 70 to 90° C. for 1 to 2 hours to obtain a polyurethane prepolymer I; then the temperature is lowered to 60 to 80° C., 20 to 30 parts by weight of a chain extender dihydroxymethylpropionic acid (DMPA, dissolved in acetone and added) and 2 to 5 parts by weight of a cross-linking agent trihydroxypropionic acid (DMPA) are added; Propane (TMP) reacts for 2 to 3 hours to obtain polyurethane prepolymer II; then continue to cool to 55 to 60°C, add 20 to 30 parts by weight of hydroxyethyl acrylate (HEA) and 90 to 95 parts by weight of pentaerythritol triacrylate (PETA) as two end-capping agents, and 0.01 to 0.05 parts by weight of p-methoxyphenol as a polymerization inhibitor for graft copolymerization, and after cooling the reaction product, add a neutralizing agent triethylamine (TEA) and water, stir and mix evenly, and then remove the solvent acetone to obtain a pentaerythritol triacrylate modified polyurethane anion resin emulsion. The solid content of the obtained pentaerythritol triacrylate modified polyurethane anion resin emulsion is 20±2%.
[0016] As an embodiment of the present invention, the pH regulator is selected from one or more of ammonia water, triethanolamine, triethylamine, and N,N-dimethylethanolamine.
[0017] As an embodiment of the present invention, the curing agent is isocyanate and / or aziridine.
[0018] As an embodiment of the present invention, the anchoring agent is a titanate coupling agent.
[0019] As an embodiment of the present invention, the leveling wetting agent is an acetylene glycol ethoxy compound and / or an acetylene glycol ethylene oxide compound.
[0020] As an embodiment of the present invention, the defoaming agent is polyvinyl ether.
[0021] In a second aspect, the present invention provides an antistatic BOPET film for enhancing UV printing adhesion, comprising a BOPET base film, on which an antistatic coating for enhancing UV printing adhesion is arranged, and the antistatic coating for enhancing UV printing adhesion is made of the coating material described in the present invention.
[0022] As an embodiment of the present invention, an antistatic coating for enhancing UV printing adhesion is provided on a single side of the BOPET base film.
[0023] As an embodiment of the present invention, the BOPET base film has a thickness of 10 to 14 μm, preferably 12 μm.
[0024] As an embodiment of the present invention, the thickness of the antistatic coating for enhancing UV printing adhesion is 0.05 to 0.15 μm.
[0025] In a third aspect, the present invention provides a method for preparing an antistatic BOPET film with enhanced UV printing adhesion, comprising the steps of: the PET film is longitudinally stretched and then online coated, the coating liquid adopts the coating material described in the present invention, an antistatic coating for enhancing UV printing adhesion is formed on a single side surface of the PET film, and then transversely stretched after online coating.
[0026] As an embodiment of the present invention, the online coating adopts reverse coating of a micro-gravure coating roller, the coating liquid temperature is 15-20°C, the coating machine temperature is 20±1°C, the pressure of the pressure roller is 5±0.2MPa, and the coating wet glue amount is 3-5g / m 2 .
[0027] In a fourth aspect, the present invention provides an application of an antistatic BOPET film for enhancing UV printing adhesion, namely, an application as a printing material.
[0028] The antistatic BOPET film for enhancing UV printing adhesion provided by the present invention is formed by coating the coating material provided by the present invention on the surface of the BOPET base film layer. The coating material provided by the present invention is an aqueous emulsion.
[0029] The antistatic BOPET film with enhanced UV printing adhesion provided by the present invention has a coating material with an aqueous UV curing resin added therein to introduce UV reactive functional groups. The aqueous UV curing resin is randomly mixed with an aqueous polyurethane resin emulsion after film formation to uniformly distribute the UV reactive functional groups in the coating. When UV ink printing is performed on the prepared antistatic BOPET film with enhanced UV printing adhesion, the UV ink is cured under ultraviolet light, and the UV ink combines with the UV reactive functional groups in the coating to form a covalent bond, thereby enhancing the adhesion between the UV ink and the coating and effectively improving the problem of UV ink peeling off from the coating. The aqueous UV curing resin should be added in an appropriate amount in the coating material. If the aqueous UV curing resin is added in an excessive amount, the dense UV reactive functional groups are close to each other under the thermal motion of the molecular chain, and self-polymerization reaction is easily generated during long-term storage, causing the coating to gradually become brittle, which affects the use.
[0030] A modified polythiophene antistatic agent is also added to the coating material of the present invention, and the prepared coating improves the antistatic performance of the film. The modified polythiophene antistatic agent is made of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and poly(3,4-ethylenedioxythiophene) has excellent properties such as high conductivity, good light transmittance, and excellent performance, but it is a polymer that is difficult to dissolve, melt, and process. Since sodium polystyrene sulfonate (PSS) contains a large number of hydrophilic sulfonic acid groups, after poly(3,4-ethylenedioxythiophene) (PEDOT) is doped with PSS, the non-water-soluble PEDOT conductive molecular chain and the strongly hydrophilic PSS chain are combined in the form of charge balance, stably dispersed in water, and the dispersion can be coated and dried on different substrates to form a film, which greatly improves the processing performance and has good stability and compatibility.
[0031] The water-based UV curing resin in the coating material, wherein the UV reactive functional group can combine with the UV ink under the action of ultraviolet light, thereby enhancing the adhesion between the UV ink and the coating; the coating material provided by the present invention also has an antistatic function, which can avoid mutual adsorption or adsorption on objects in the environment due to static electricity, facilitate the use of the staff, reduce the adsorption of dust particles, and has strong practicality. Under the synergistic effect of the two, the existing UV ink has improved the insufficient adhesion of the polyester film substrate surface and the problem of static electricity in downstream use, meets the needs of high-speed UV ink printing, and has strong practicality and commercial prospects. In addition, the coating material provided by the present invention is an aqueous emulsion, free of fluorine, no volatile organic compound (VOC) emissions, no odor generation, and is green and environmentally friendly.
[0032] Beneficial effects of the present invention:
[0033] (1) The antistatic BOPET film for enhancing UV printing adhesion provided by the present invention enhances the adhesion between the UV ink layer and the coating during printing by designing the coating material formula, and the UV ink still adheres well without falling off under an environmental humidity of 50% RH;
[0034] (2) The antistatic BOPET film provided by the present invention for enhancing UV printing adhesion has good antistatic performance and a surface resistance value of up to 10 6 -10 8 Ω, to meet the needs of high-speed production;
[0035] (3) The present invention adopts an online coating process to prepare an antistatic BOPET film with enhanced UV printing adhesion, and has good coating flatness, low production cost and high efficiency. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described in detail below. It should be understood by those skilled in the art that the specific implementation is only to help understand the present invention and should not be regarded as a specific limitation of the present invention.
[0037] It should be noted that, unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art.
[0038] The raw materials used in the following examples and comparative examples are described as follows. Unless otherwise specified, they are all commercially available conventional products and can be purchased.
[0039] Poly(3,4-ethylenedioxythiophene): polystyrene sulfonic acid aqueous dispersion stock solution (purchased from Changxing Chemical, G9106A-1), solid content of 5%;
[0040] The waterborne polyurethane resin emulsion is an anionic waterborne polyurethane resin emulsion (purchased from Shanghai Bo Rui Ao, AU2848);
[0041] The curing agent is aziridine curing agent (purchased from Covestro, XP2661);
[0042] Titanate coupling agent (purchased from Nanjing Nengde, TCA-K46B);
[0043] Alkyne glycol ethoxylate (purchased from Shanghai Zicheng, GS2374).
[0044] In the following embodiments, the antistatic BOPET film with enhanced UV printing adhesion provided by the present invention has an overall process flow of the preparation method as follows: PET resin melting → extrusion casting → longitudinal stretching → corona treatment → online coating → transverse stretching → traction and winding → slitting and packaging. Compared with the ordinary BOPET film (biaxially oriented polyethylene terephthalate film), the main difference in the preparation method is that an online coating process is added between the longitudinal stretching unit and the transverse stretching unit. The PET film after longitudinal stretching is coated online, and the coating liquid adopts the coating material described in the present invention to form an antistatic coating that enhances UV printing adhesion on the single side surface of the PET film, and then transverse stretching treatment is performed after online coating. The online coating adopts reverse coating with a micro-gravure coating roller, the coating liquid temperature is 15-20°C, the coating machine temperature is 20±1°C, the pressure of the pressure roller is 5±0.2MPa, and the coating wet glue amount is 3-5g / m 2 .
[0045] Specifically, the preparation process of the antistatic BOPET film with enhanced UV printing adhesion provided by the present invention is as follows: the PET polyester melt produced in the polyester synthesis process is transported to a twin-screw main extruder through a melt pipeline, and at the same time, film-grade PET slices, silicon-containing PET slices and recycled slices are put into a twin-screw auxiliary extruder, and after being melted and plasticized by the extruder, the PET melt is extruded onto a casting roller through a Y-shaped die head, and rapidly cooled on the low-temperature casting roller to form a thick sheet with a crystallinity of less than 3%, and then enters a longitudinal stretching unit, and longitudinally stretches through the speed difference between the front and rear rollers, and then enters a corona treatment unit to increase the surface energy of the film to more than 52 dynes, and then online coating is performed to prepare a coating, and then transversely stretched to obtain a BOPET film, and then traction, winding, slitting and packaging are performed to obtain the antistatic BOPET film with enhanced UV printing adhesion.
[0046] The parameters involved in the above preparation process include: main / auxiliary extruder temperature of 260-280°C; casting roller temperature of 25±1°C; longitudinal stretching temperature of 80-100°C, stretching ratio of 3.2-4.0; corona machine voltage of 15±0.5kV, speed ratio of 0±0.1%; coating machine temperature of 20±1°C, pressure roller pressure of 5±0.2MPa, coating wet glue amount of 3-5g / m 2 ; The transverse stretching temperature is 100-130°C, the setting temperature is 220-235°C, and the stretching ratio is 3.8-4.5.
[0047] The following is a detailed explanation through specific examples.
[0048] Example 1
[0049] This embodiment provides a coating material, which is made of the following raw materials in percentage by mass:
[0050]
[0051] The preparation method of the modified polythiophene antistatic agent is as follows: the pH value of the poly(3,4-ethylenedioxythiophene): polystyrene sulfonic acid aqueous dispersion stock solution is adjusted to 7.5 with ammonia water, and then mixed with anionic waterborne polyurethane resin emulsion, titanate coupling agent and isopropanol, and stirred rapidly for 2 hours, and then diluted by 3 times with pure water, and continued to stir for 4 hours until completely mixed, to obtain the modified polythiophene antistatic agent. The mass ratio of the poly(3,4-ethylenedioxythiophene): polystyrene sulfonic acid aqueous dispersion stock solution, anionic waterborne polyurethane resin emulsion, titanate coupling agent, and isopropanol is 5:15:0.3:30. The solid content of the modified polythiophene antistatic agent is 10%.
[0052] The water-based UV curable resin is a polyurethane anion resin modified by pentaerythritol triacrylate, and the preparation method is as follows: 100 parts by weight of isophorone diisocyanate (IPDI), 92 parts by weight of polypropylene glycol (PPG-1000), and 0.3 parts by weight of dibutyltin dilaurate catalyst are stirred and reacted at 80-85° C. for 1 hour to obtain polyurethane prepolymer I; the temperature is lowered to 65° C., 25 parts by weight of chain extender dihydroxymethylpropionic acid (DMPA, dissolved in acetone and then added) and 4 parts by weight of cross-linking agent trihydroxypropane are added. (TMP) was reacted for 3 hours to obtain polyurethane prepolymer II; then the temperature was continued to be lowered to 58°C, 25 parts by weight of hydroxyethyl acrylate (HEA) and 90 parts by weight of pentaerythritol triacrylate (PETA) as two end-capping agents, and 0.02 parts by weight of p-methoxyphenol as an inhibitor were added to carry out graft copolymerization reaction, and after the reaction product was cooled, a neutralizing agent triethylamine (TEA) and water were added, and after stirring and mixing evenly, the solvent acetone was removed to obtain a polyurethane anionic resin emulsion modified with pentaerythritol triacrylate having a solid content of 20%.
[0053] The coating material provided in this embodiment is prepared by mixing various raw materials, stirring them evenly, and preparing an aqueous emulsion for use.
[0054] The antistatic BOPET film with enhanced UV printing adhesion was prepared using the coating material provided in this embodiment, and the preparation process is as follows:
[0055] The PET polyester melt produced in the polyester synthesis process is transported to the twin-screw main extruder through a melt pipeline, and the film-grade PET slices, silicon-containing PET slices and recycled slices are simultaneously fed into the twin-screw auxiliary extruder. After being melted and plasticized by the extruder, the PET melt is extruded onto the casting roll through a Y-shaped die head, and rapidly cooled on the low-temperature casting roll to form a thick sheet with a crystallinity of less than 3%. The thick sheet enters the longitudinal stretching unit, and is longitudinally stretched through the speed difference between the front and rear rollers, and then enters the corona treatment unit to increase the surface energy of the film to more than 52 dynes.
[0056] Then, the coating is prepared by online coating, and the coating liquid adopts the coating material provided in this embodiment. An antistatic coating for enhancing UV printing adhesion is formed on the single side surface of the PET film. The online coating adopts reverse coating with a micro-gravure coating roller. After the online coating, it is transversely stretched to obtain a BOPET film, and then it is pulled, rolled, slit and packaged to obtain an antistatic BOPET film for enhancing UV printing adhesion.
[0057] The parameters involved in the above preparation process include: main / auxiliary extruder temperature is 260-280℃; casting roller temperature is 25±1℃; longitudinal stretching temperature is 80-100℃, stretching ratio is 3.6; corona machine voltage is 15±0.5kV, speed ratio is 0±0.1%; coating liquid temperature is 15-20℃, coating machine temperature is 20±1℃, pressure roller pressure is 5±0.2MPa, coating wet glue amount is 4.1g / m 2 ; The transverse stretching temperature is 100-110°C, the setting temperature is 220-235°C, and the stretching ratio is 4.0.
[0058] The prepared antistatic BOPET film for enhancing UV printing adhesion has a BOPET base film thickness of 12 μm and an antistatic coating for enhancing UV printing adhesion thickness of 0.10 μm.
[0059] Example 2
[0060] This embodiment provides a coating material, which is made of the following raw materials in percentage by mass:
[0061]
[0062] Wherein, the modified polythiophene antistatic agent and the water-based UV curing resin are the same as those in Example 1.
[0063] The coating material provided in this embodiment is prepared by mixing various raw materials, stirring them evenly, and preparing an aqueous emulsion for use.
[0064] By using the coating material provided in this embodiment, an antistatic BOPET film with enhanced UV printing adhesion was prepared with reference to Example 1. The prepared antistatic BOPET film with enhanced UV printing adhesion had a BOPET base film thickness of 12 μm and an antistatic coating thickness of 0.08 μm for enhancing UV printing adhesion.
[0065] Example 3
[0066] This embodiment provides a coating material, which is made of the following raw materials in percentage by mass:
[0067]
[0068] Wherein, the modified polythiophene antistatic agent and the water-based UV curing resin are the same as those in Example 1.
[0069] The coating material provided in this embodiment is prepared by mixing various raw materials, stirring them evenly, and preparing an aqueous emulsion for use.
[0070] By using the coating material provided in this embodiment, an antistatic BOPET film with enhanced UV printing adhesion was prepared with reference to Example 1. The prepared antistatic BOPET film with enhanced UV printing adhesion had a BOPET base film thickness of 12 μm and an antistatic coating thickness of 0.11 μm.
[0071] Comparative Example 1
[0072] This comparative example provides a BOPET corona film, and the preparation process is as follows:
[0073] The PET polyester melt produced in the polyester synthesis process is transported to the twin-screw main extruder through a melt pipeline, and the film-grade PET slices, silicon-containing PET slices and recycled slices are simultaneously fed into the twin-screw auxiliary extruder. After being melted and plasticized by the extruder, the PET melt is extruded onto the casting roll through a Y-shaped die head, and rapidly cooled on the low-temperature casting roll to form a thick sheet with a crystallinity of less than 3%. The sheet enters the longitudinal stretching unit, and is longitudinally stretched through the speed difference between the front and rear rollers. The sheet then enters the transverse stretching unit for transverse stretching treatment, and then passes through the winding corona treatment unit to increase the film surface energy to more than 52 dynes; after traction, winding, slitting and packaging, the BOPET corona film is obtained. The thickness of the BOPET corona film is 12μm.
[0074] The parameters involved in the above preparation process include: main / auxiliary extruder temperature of 260-280°C; casting roller temperature of 25±1°C; longitudinal stretching temperature of 80-100°C, stretching ratio of 3.6; corona machine voltage of 15±0.5kV, speed ratio of 0±0.1%; transverse stretching temperature of 100-110°C, shaping temperature of 220-235°C, stretching ratio of 4.0.
[0075] The antistatic BOPET films prepared in the above Examples 1-3 and the BOPET corona film provided in Comparative Example 1 were used for UV ink printing, and the performance of the obtained printed products was tested.
[0076] UV ink printing: Brotech flexo press, UV power 270mW / cm 2 , using Flint UFO flexographic UV ink (blue) for 5cc large solid printing.
[0077] The ink fastness of the printed products was tested and the coating simulation pollution experiment was carried out.
[0078] Ink fastness test: Lay the printed sample flat, stick Scotch 810 tape to the ink of the test sample in the longitudinal direction of printing, and use a 2kg roller to move back and forth twice. After standing at room temperature for 30 minutes, quickly tear off the Scotch 810 tape at 180 degrees to observe whether there is ink on the tape and the degree of ink shedding of the sample. Description is divided into:
[0079] No shedding---Excellent grade;
[0080] Spot shedding, shedding area <5%, no base film visible - good grade;
[0081] Flakes fall off, the falling area is less than 10%, and the base film is not visible - qualified grade;
[0082] Flaking, shedding area > 10%, base film visible - unqualified grade.
[0083] Coating simulation pollution experiment: The release surface of the online silicone release BOPET film was placed in contact with the printed surface of the sample with printed ink, and 70g / cm 2 Pressure, placed at room temperature (23℃, 50% RH) and 70℃ for 24h, to obtain simulated contaminated printable samples. The simulated contaminated printable samples were then subjected to ink fastness test. Specifically: lay the simulated contaminated printable sample flat, stick the Scotch 810 tape to the ink of the test sample in the longitudinal direction of printing, and use a 2kg roller to go back and forth twice. After standing at room temperature for 30min, quickly tear off the Scotch 810 tape at 180° to observe whether there is ink on the tape and the degree of ink shedding of the sample.
[0084] Surface resistance value test: Lay the film with the coating surface facing up on a glass plate, press the film firmly with a handheld resistance tester HZR MODLE100 to ensure that the positive and negative electrodes of the tester are tightly attached to the coating surface (without gaps), turn on the test button, and wait for about 1 minute to complete the test.
[0085] The above test results are specifically shown in Table 1 below.
[0086] Table 1
[0087]
[0088] It can be seen from Table 1 that the antistatic BOPET films provided by Examples 1-3 of the present invention have low surface resistance and good antistatic performance; and the adhesion between the UV ink layer and the coating is high during printing, and the ink does not fall off or substantially does not fall off.
[0089] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. A coating material, characterized in that: Made of the following raw materials in percentage by mass:
2. The coating material according to claim 1, characterized in that The preparation method of the modified polythiophene antistatic agent is as follows: adjusting the pH value of the poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid aqueous dispersion stock solution to 7.3-7.6 with ammonia water, then mixing it with an aqueous polyurethane resin emulsion, a titanate coupling agent and isopropanol, and then diluting it with water to obtain the modified polythiophene antistatic agent; The mass ratio of the poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid aqueous dispersion stock solution, the aqueous polyurethane resin emulsion, the titanate coupling agent, and the isopropanol is: (1-5): (10-20): (0.1-1): (10-30); Preferably, the solid content of the modified polythiophene antistatic agent is 10% to 20%.
3. The coating material according to claim 1 or 2, characterized in that: The aqueous polyurethane resin emulsion is selected from anionic aqueous polyurethane resin emulsion and nonionic aqueous polyurethane resin emulsion.
4. The coating material according to claim 3, characterized in that The water-based UV curable resin is a polyurethane anion resin modified by pentaerythritol triacrylate.
5. The coating material according to claim 1, characterized in that The pH regulator is selected from one or more of ammonia water, triethanolamine, triethylamine, and N,N-dimethylethanolamine; and / or the curing agent is isocyanate and / or aziridine; and / or the anchoring agent is a titanate coupling agent; and / or the leveling wetting agent is an acetylene glycol ethoxy compound and / or an acetylene glycol ethylene oxide compound; and / or the defoaming agent is polyethylene ether.
6. An antistatic BOPET film for enhancing UV printing adhesion, characterized in that: The invention comprises a BOPET base film, on which an antistatic coating for enhancing UV printing adhesion is arranged, and the antistatic coating for enhancing UV printing adhesion is made of the coating material according to any one of claims 1 to 5.
7. The antistatic BOPET film for enhancing UV printing adhesion according to claim 6, characterized in that: The thickness of the BOPET base film is 10-14 μm, preferably 12 μm; the thickness of the antistatic coating for enhancing the adhesion of UV printing is 0.05-0.15 μm.
8. A method for preparing an antistatic BOPET film with enhanced UV printing adhesion according to claim 6 or 7, characterized in that: The method comprises the following steps: the PET film is longitudinally stretched and then coated online, the coating liquid adopts the coating material described in any one of claims 1 to 5, an antistatic coating for enhancing UV printing adhesion is formed on a single side surface of the PET film, and then transverse stretching is performed after the online coating.
9. The preparation method according to claim 8, characterized in that: Online coating uses micro-gravure coating roller reverse coating, the coating liquid temperature is 15-20℃, the coating machine temperature is 20±1℃, the pressure roller pressure is 5±0.2MPa, and the coating wet glue amount is 3-5g / m 2 .
10. Use of the antistatic BOPET film for enhancing UV printing adhesion as claimed in claim 6 or 7 as printing material.
Citation Information
Patent Citations
Polyester thin film manufacturing method
CN106891514A
Colorful ultraviolet (UV) light solidifying paint
CN102212311A
Preparation method and application of neutral polythiophene antistatic paint
CN105820746A
Enhanced UV ink printing film and preparation method thereof
CN116285543A